The Role of Banana (Musa balbisiana Colla) Peel Floss as Functional Food Matrix to Alleviate Chronic Stress - Meliala, Andreanyta; Narwidina, Paramita; Supriyanto, Irwan; Sumarno, Yogi Tri; Pratama, Yanasta Yudo; Damayanti, Rian (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Banana peel (Musa balbisiana Colla) already has a diverse variety of nutritional benefits, but its perishable nature necessitates additional food processing, one of which is banana peel floss. AIM: The objective of this study was to examine the antidepressant effects of banana peel floss in experimental animals subjected to chronic mild stress (CMS) for 6 weeks. METHODS: Animals were randomly assigned into five groups. The first group was fed a control diet without CMS as a negative control. The other four groups were exposed to CMS and fed a control diet as a positive control, with three of the five groups fed a control diet supplemented with 15%, 30%, and 60% banana peel floss. The tail suspension test (TST) and the Morris water maze were used as behavioral parameters in this study (MWM). Cortisol and serotonin levels were measured in two stages: after CMS exposure or before banana peel floss intervention, and after 4 weeks of banana peel floss intervention. RESULTS: The results showed that the immobility time in TST and escape latency in the MWM test were significantly reduced in the groups supplemented with 15% and 30% banana peel floss, respectively. Furthermore, we observed a significant association between serotonin and cortisol levels and also between the duration of immobility time in TST and serotonin levels. CONCLUSIONS: The administration of banana peel floss caused significant changes in plasma serotonin concentrations, implying that the presence of dietary fiber, tryptophan, and bioactive components in banana peel floss can reduce stress-induced depression by regulating cortisol levels and increasing serotonin levels.